Integrasi literasi digital, informasi, dan keagamaan sebagai upaya meningkatkan kualitas pembelajaran di era digital - Syukur, Najma Mumtaz (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has brought about significant changes in the world of education and requires improvements in the qualitu of learning that align with the needs of the digital age. This study aims to examine the integration of digital literacy, information literacy, and religious literacy to improve the quality of learning in the digital age. The method used in this study is a literature review utilizing vatious journal articles and references related to digital literacy, information literacy, and religious literacy. The results of the study indicate that reading and writing skills in the digital age are crucial fro helping students use technology effectively and productively. Information literacy helps students yhink critically when selecting and disseminating information the obtain from digital media. Meanwhile, religious literacy plays a vital role in shaping students’ character, morals, and ethics when using technology. The integration of these three literacies can crate a more interactive, innovative, and meaningful learning experience, as well as help foster a generation that is intelligent, critical, and of goo character. Thus, the integration of digital, information, dan religious literacy is a crucial step toward improving the quality of learning in the digital age.